Experimental Investigation on Stirring Rate Affecting Bubble Structure of Resin Anchor Agent and Anchoring Strength - Jiaguang Kan; Yuantian Sun; Yifan Wang; Sen Yang; Peng Wang (Advances in Materials Science and Engineering)
The function of a resin anchoring agent is to bond the rock of a borehole wall with the body of the anchor so the anchor can play an effective supporting role. The anchoring effect is related to the performance of the resin anchoring agent used and to the stirring rate applied during the anchor installation process. In this report, the stirring rate of the resin anchoring agent is evaluated and discussed in terms of how it affects pore structure and anchoring strength. When the stirring rate is in the range of 400–950 r/min, the uniaxial compressive strength of the resin anchoring agent increases proportionally with the stirring rate, and the compressive strength corresponding to the maximum stirring rate is 15.1% greater than that corresponding to the minimum stirring rate. Conversely, the pore size of the foam inside the resin anchoring agent is inversely proportional to the stirring rate, and the pore size corresponding to the maximum stirring rate is 15.1% smaller than that corresponding to the minimum stirring rate. The anchoring strength increases proportionally with the stirring rate when the stirring rate is between 400 and 800 r/min. Specifically, the anchoring strength associated with the maximum stirring rate is 9.2% greater than the anchoring strength corresponding to the minimum stirring rate. As the stirring time increases from 20 to 60 s, the anchoring force first increases and then decreases, with the optimal stirring time determined to be about 50 s. The results presented herein can be applied to improve anchor installation technology and the anchoring strength of resin anchoring agents.